FTT:Heat — A simulation model for technological change in the European residential heating sector - Knobloch, Florian; Pollitt, Hector; Chewpreecha, Unnada; Lewney, Richard; Huijbregts, Mark A.J.; Mercure, Jean-Francois (Energy policy, 2021)
We introduce a new bottom-up model for simulating Future Technology Transformations in the European residential heating sector, FTT:Heat. The model simulates the uptake and replacement of heating technologies by households in all individual Member States up to 2050, and allows to simulate the potential effect of real-world policy instruments aiming at an increased uptake of low-carbon technologies. It features an explicit representation of households' technology choices, based on observed preferences and non-linear diffusion dynamics. Decision-makers are modelled as individual households, which are subject to limited information and bounded rationality. Their decisions reflect behavioural factors and preferences at the micro level, and may result in sub-optimal outcomes from a macroeconomic perspective. For demonstration, we simulate policy mixes for reaching the EU's 2030 renewable heating targets in each Member State. Under current diffusion trends, some countries are estimated to continue an ongoing transition towards renewable heating, while others would hardly see any decarbonisation. For increasing the share of renewable heating by at least ten percentage points until 2030, 20 Member States need to introduce additional policies, the necessary stringency of which differs between countries. Due to the slow turnover of heating systems, resulting cost increases faced by households could persist over decades. •New bottom-up model for simulating the uptake of heating technologies by households.•Allows to simulate the effect of various market-based and regulatory policies.•Technology uptake subject to non-linear diffusion dynamics and bounded rationality.•Results indicate large diversity of current trends in technology uptake across EU.•Necessary policy effort for increased share of renewable heating differs widely.